Islamic Organisations, Inter-religious Philanthropy and Welfare in Disaster: Some Experiences from West Nusa Tenggara, Indonesia - Triantini, Zusiana Elly; Susetiawan, Susetiawan; Mas'udi, Wawan (Universitas Islam Negeri Mataram, 2024)
This article presents a case study of successful inter-religious philanthropy practices in the context of a natural disaster in Lombok, West Nusa Tenggara, Indonesia. Previous studies have shown that inter-religious philanthropy often has a hidden ideological mission, prompting resistance from the local community. This study offers a new perspective by depicting the inter-religious philanthropy practices in West Nusa Tenggara, Indonesia, after the 2018 earthquake. The data show that inter-religious philanthropists work as non-state actors mitigating post-disaster poverty with various programs. The findings also indicate that optimizing the inter-religious network and actors in disaster management of the 2018 earthquake, such as distributing aid to the victims-championed by Islamic organizations, such as Nahdlatul Ulama and Muhammadiyah, did not only help solve poverty and welfare problems but also strengthened inter-religious relations and solidarity in the community.